The Imagination Library Program and Kindergarten Readiness: Evaluating the Impact of Monthly Book Distribution. (March 2017) - Ridzi, Frank; Sylvia, Monica; Qiao, Xiaofen; Craig, Jeff
Literature suggests that reading to children can have a significant impact on their early literacy development and long-term school performance. We examine whether consistent participation (i.e., three or more years) in Dolly Parton's Imagination Library (DPIL), a book distribution program that provides one book per month to children ages birth through five, is associated with higher kindergarten readiness. This study examines 2, 731 incoming kindergartners in the Syracuse City School District in 2013 and 2014 using the AIMSweb Letter Naming Fluency (LNF) test to assess kindergarten readiness. LNF is frequently identified as the best single indicator of risk for reading failure and has been shown to have a strong ability to predict future reading, vocabulary, and language development. Examining both the entire population and propensity score matched groups, we find that a significantly higher percentage of those consistently participating in DPIL were considered as ready for kindergarten. This difference remained even after controlling for key demographic variables.